2012
DOI: 10.1073/pnas.1215696110
|View full text |Cite
|
Sign up to set email alerts
|

Smg1 haploinsufficiency predisposes to tumor formation and inflammation

Abstract: SMG1 is a member of the phosphoinositide kinase-like kinase family of proteins that includes ATM, ATR, and DNA-PK, proteins with known roles in DNA damage and cellular stress responses. SMG1 has a well-characterized role in nonsense-mediated decay as well as suggested roles in the DNA damage response, resistance to oxidative stress, regulation of hypoxic responses, and apoptosis. To understand the roles of SMG1 further, we generated a Genetrap Smg1 mouse model. Smg1 homozygous KO mice were early embryonic leth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 46 publications
(63 reference statements)
8
68
0
Order By: Relevance
“…Moreover, Smg1 has been showed to be involved in the predisposition to tumor formation and inflammation in Smg1 heterozygous mice; this mouse model presents elevated basal tissue and serum cytokine levels—indicating low-level inflammation—and can progress to chronic inflammation or enhanced cancer development. Therefore, this is a model of inflammation-enhanced cancer development (Roberts et al, 2013), also suggesting that Smg1 is a tumor suppressor (Du et al, 2014). To our knowledge, the possibility to target inflammation through Smg1 has never been applied to medulloblastoma until now.…”
Section: Resultsmentioning
confidence: 96%
“…Moreover, Smg1 has been showed to be involved in the predisposition to tumor formation and inflammation in Smg1 heterozygous mice; this mouse model presents elevated basal tissue and serum cytokine levels—indicating low-level inflammation—and can progress to chronic inflammation or enhanced cancer development. Therefore, this is a model of inflammation-enhanced cancer development (Roberts et al, 2013), also suggesting that Smg1 is a tumor suppressor (Du et al, 2014). To our knowledge, the possibility to target inflammation through Smg1 has never been applied to medulloblastoma until now.…”
Section: Resultsmentioning
confidence: 96%
“…22 SMG-1-knockout mice are embryonically lethal, but haploinsufficiency predisposes to a whole range of tumor formation and inflammation, demonstrating that SMG-1 is a tumor suppressor. 23 Also, diminished SMG-1 expression has been shown in HPV-positive head and neck squamous cell carcinoma and has been suggested to contribute to the enhanced response to therapy. It was previously reported that SMG-1 depletion in U2OS cells led to defects in phosphorylation of p53 on Ser15 and compromised the G 1 /S checkpoint upon treatment with IR.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, mTOR has also been shown to have important roles in B cell development; mTORC1 is required for differentiation past the pre‐B cell stage, possibly as a result of regulation of glycolysis (see below for more detail) . mTORC2 in contrast is important for the development of mature B cells . Further activation of mTOR contributes to toll‐like receptor induced emergency myelopoiesis .…”
Section: Mtormentioning
confidence: 99%
“…It is one of the least studied members of the PIKK family. Two independent mouse models have shown that complete loss of SMG1 is early embryonic lethal . SMG1 has been implicated in the control of a wide range of cellular processes including DNA damage responses, cell cycle regulation, apoptosis, hypoxia responses, and RNA stability.…”
Section: Smg1mentioning
confidence: 99%
See 1 more Smart Citation